Drought tolerant and physiologically efficient genetic resources for rainfed castor (Ricinus communis L.): CASTOR GERMPLASM ACCESSIONS FOR DROUGHT TOLERANCE - P LAKSHMAMMA; LAKSHMI PRAYAGA; K ALIVELU; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2021)
Six identified germplasmaccessions(RG 111, RG 298, RG 1437, RG 1494, RG 1826, RG 2797) with good root volume, dry weight and low drought susceptibility index (low DSI) along with two checks (48-1, DCH-519) were screened to understand their performance under rainfed conditions during kharif 2014 and 2015. Secondary spikes were produced only during 2015 in RG 2797. Germplasm lines viz., RG 298 and RG 1826 produced tertiary spikes during both years. RG 111, RG 1437 and RG 1494 recorded tertiary seed yield during 2015 only. Pooled mean seed yield data showed higher primary seed yield in RG 1494 and RG 2797. Secondary seed yield was higher in RG 1437 followed by RG 298 and RG 1494. Tertiary seed yield was more in RG 1826 and RG 298. Among the genotypes studied, RG 1494 (101 g/pl.) followed by RG 1826 (96 g/pl.) and RG 298 (91 g/pl.) with significantly higher total seed yield (pooled average of two years) showed better performance. RG 298 and RG 1826 recorded high harvest index (HI) of 36.1% and 42.6% respectively. RG 1494 recorded significantly higher stem and leaf weight at harvest but with low HI (31.3%) compared to RG 298 and RG 1826, which indicated the stay green trait of this genotype. Genotypes, RG 1494, RG 298 and RG 1826 with good root growth, high seed yield under rainfed conditions and with drought tolerance could be used in breeding programs.